Designing Bioclimatic Buildings to Minimize Energy Consumption: A Study on the Role of Education - Giannarou, Sofia; Tsatiris, Michael (New Approaches in Engineering Research Vol. 8, 2021)
Globally, one of the major issues that humanity is dealing with today is environmental pollution caused by over-consumption of conventional forms of energy, with the building sector leading the way, resulting in a change in the climate and nature, as well as a threat to the lives of people, animals, and plants. The realisation of the need to reduce energy usage has led to an endeavour to improve the energy performance of buildings by employing bioclimatic architectural concepts. The aim is to ensure thermal comfort conditions for building users, exploiting the favorable climatic conditions prevailing in each area. It aims to use renewable and inexhaustible energy sources like the sun and air. In particular, it requires the commitment of solar radiation and the protection from cold winds during the winter and the use of cool winds, as well as protection from the hot rays of the sun during the summer. In this article, taking into account the fact that in Greece sustainability has begun to concern the population of the country and governments very recently. The result of the indifference or ignorance of the Greeks in matters of sustainability was that most of the building stock in the country to be unsustainable, over consuming buildings. The purpose of this study is to investigate how Greece will be able to deal with this adverse situation in terms of sustainability, proposing ways to educate students, professionals / engineers and building users to gain environmental awareness and at the same time emphasize the multiple benefits of bioclimatic planning for the environment and the economy. Bioclimatic architecture should be the rule, not the exception.